FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SELF CARE PADA PASIEN DIABETES MELITUS TIPE II DI RUMAH SAKIT ANUTAPURA PALU - Sri Yulianti (CHMK Applied Science Journal, 2021)
ABSTRACT Modern life style with a lot of menu of food and unhealthy life style could caused increasing of degenerative disease and one of it is Diabetic Mellitus. The problem could minimalised if the patient have self efficacy, family support and health insurance in arrangement of the disease by doing self care. The aims of this research to obtain the correlation factors of self care toward type II of diabetic mellitus patient in Anutapura General Hospital, Palu. This is quantitative research with correlation method of cross sectional approached. Total of population is 112 respondents, but sampling only 32 respondents that taken by accidental sampling technique.data analysed by chi square test. The result shown that most of respondents have good self efficacy (81.2%), duration time with DM suffering experiences >5 years (53,1%), have good family support (78,1%) and have health insurance (87,5%). The result of chi-square bivariate analyses found that self efficacy have p value 0,012<0,05, long suffering have p value 0,028<0,05, family support have p value 0,000<0,05 and health insurance have p value 0,025<0,05. Conclusion of this research that all independent variables have significant correlation with dependent variables (self care) toward type II of diabetic mellitus patient. Keyword: self efficacy, long suffering, family support, health insurance, self care